TINJAUAN YURIDIS PENYIDIKAN TINDAK PIDANA PERAIRAN LAUT DI AREA ZONA EKONOMI EKSKLUSIF INDONESIA - La Ode Ali Mustafa; Irfan Irfan (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2021)
The main objective of this research is to find out the process of investigation marine crimes in the Indonesian Exclusive Economic Zone and how to apply legal sanction to marine crimes in that area. This research is normative. The technique of collecting data with literature study is reading book that match the research title. Data analysis is descriptive and then draws conclusion. Based on the results of the research, it can be concluded that the investigation process of marine crimes in the Indonesian exclusive Economic Zone is carried out with the stages of ship detection, ship investigation and the follow up. The effectiveness of law enforcement in the ZEEI area is influenced by the legal factors themselves, their apparatus, facilities and infrastructure, society and culture. The application against perpetrators of criminal acts in the marine area of the Indonesian exclusive Economic Zone (ZEEI) that every violation committed by a ship or an individual is subject to action in accordance with the applicable law if there is sufficient initial evidence and for the offender Indonesian citizens were immediately directed to the nearest base on the orders of investigations for immediate processing.